1997
DOI: 10.1183/09031936.97.10071614
|View full text |Cite
|
Sign up to set email alerts
|

Breathing pattern and respiratory mechanics in patients with amyotrophic lateral sclerosis

Abstract: These results suggest a progressive deterioration in breathing pattern and in respiratory muscle strength with progression of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
50
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 35 publications
(42 reference statements)
2
50
0
2
Order By: Relevance
“…A truncated VT has been suggested as an alteration in ventilatory control that ultimately leads to chronic CO 2 retention (23). In another study (36), longitudinal data on breathing pattern and respiratory mechanics in ALS patients showed evidence consistent with a restrictive ventilatory pattern derived from progressive weakness of respiratory muscle function. Patients compensated for a decline in respiratory muscle function by demonstrating a rapid shallow breathing pattern (i.e., increasing f and decreasing VT).…”
Section: Discussionmentioning
confidence: 81%
“…A truncated VT has been suggested as an alteration in ventilatory control that ultimately leads to chronic CO 2 retention (23). In another study (36), longitudinal data on breathing pattern and respiratory mechanics in ALS patients showed evidence consistent with a restrictive ventilatory pattern derived from progressive weakness of respiratory muscle function. Patients compensated for a decline in respiratory muscle function by demonstrating a rapid shallow breathing pattern (i.e., increasing f and decreasing VT).…”
Section: Discussionmentioning
confidence: 81%
“…In addition to weakness of peripheral muscles, respiratory muscle weakness develops during the course of the disease, leading to reduced alveolar ventilation and respiratory failure, which is the main cause of death in ALS. 1,2 A randomized controlled trial showed improvement in survival and quality of life (QoL) in ALS patients treated with noninvasive ventilation (NIV). 3 Although survival in the subgroup of patients with severe bulbar impairment did not improve, small improvements in QoL were observed.…”
Section: Discussionmentioning
confidence: 99%
“…ure, loss of independence, and mortality (10,16,27,28,32). In patients with diabetic neuropathy, localized denervation of small foot muscles leads to foot deformities, a major risk factor for ulcers and amputations (1,2,13,19,30).…”
mentioning
confidence: 99%